2017
DOI: 10.15376/biores.12.3.5801-5811
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Recycled Polypropylene Composites Reinforced with Rice Straw Lignin

Abstract: Recycled polypropylene (RPP) and lignin represent by-products produced in enormous amounts worldwide that remain underutilized. This study used rice straw lignin as a filler at various concentrations (0% to 70% w/w) in RPP and virgin polypropylene (PP) composites by melt blending. Structural and morphological alterations of lignin were analyzed by Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM), respectively. Mechanical properties were evaluated using a universal testing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…At time, both the forces between various molecules and the hydrogen bonds formed between the interfaces increase, which enhances the mechanical properties of PLA. However, due to the interaction of hydrophobic and π‐π bonds between microsphere molecules, [ 30 ] microspheres would agglomerate with the increase of NPA‐60 content. NPA‐60 could not uniformly disperse in the pure PLA matrix, resulting in the decline of the mechanical properties of composites.…”
Section: Resultsmentioning
confidence: 99%
“…At time, both the forces between various molecules and the hydrogen bonds formed between the interfaces increase, which enhances the mechanical properties of PLA. However, due to the interaction of hydrophobic and π‐π bonds between microsphere molecules, [ 30 ] microspheres would agglomerate with the increase of NPA‐60 content. NPA‐60 could not uniformly disperse in the pure PLA matrix, resulting in the decline of the mechanical properties of composites.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has also been reported that the lignin content has a negative effect on the tensile strength of PP matrix composites, while increasing the modulus. 39 For instance, Bledzki et al 40 stated that jute fibers are strong but brittle and have a low elongation at break because of its high lignin content (up to 20%). Furthermore, as previously mentioned, differences in the structural properties of the natural fibers can also affect their mechanical properties together with the lignocellulosic nature of the fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The materials were then weighed to the nearest 0.001 G and mixed based on their weight pecentages (Table 4) in a rotary mixer, Santam Co., Iran for 5 min. 25 The obtained mixture was poured in a die of 28 × 28 × 1.3 cm and pressed under a hydraulic hot press, Santam Co., Iran at 185°C (35 bar, 18 min). The manufactured samples were then cold pressed at the same pressure for 10 min to release the incurred stresses.…”
Section: Methodsmentioning
confidence: 99%